2002
DOI: 10.1034/j.1600-0897.2002.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Induced Blocking Factor (PIBF) Mediates Progesterone Induced Suppression of Decidual Lymphocyte Cytotoxicity

Abstract: The results indicate possible role for PIBF, as a mediator of progesterone in regulation of DL cytolytic activity at the maternal-foetal (M-F) interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 31 publications
1
42
2
2
Order By: Relevance
“…There is a significant loss of cytotoxic T lymphocytes (CTL) and NK cells in the FRT during the luteal phase [47,48]. Progesterone exerts a strong immunosuppressive effect by blocking CTL-mediated killing by inhibition of perforin expression [49]. Gene profiling studies of the endometrium revealed that there is more robust appearance of class II molecule upregulation (HLA-DPA1, DPB1, DQB1, and DRA), complement pathway (SERPING1, C1, C1q, C3A and C5A), secretoglobin as well as a variety of NK cell receptors in the late-secretory phase [50].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant loss of cytotoxic T lymphocytes (CTL) and NK cells in the FRT during the luteal phase [47,48]. Progesterone exerts a strong immunosuppressive effect by blocking CTL-mediated killing by inhibition of perforin expression [49]. Gene profiling studies of the endometrium revealed that there is more robust appearance of class II molecule upregulation (HLA-DPA1, DPB1, DQB1, and DRA), complement pathway (SERPING1, C1, C1q, C3A and C5A), secretoglobin as well as a variety of NK cell receptors in the late-secretory phase [50].…”
Section: Discussionmentioning
confidence: 99%
“…From targets' prediction data, we found upregulated miRNAs (hsa-miR-519a-1 and hsa-miR-520h) in decidua and low expressed miRNA (hsa-miR-520f) in villus of RSA patients, all target to LIF (Supplementary Table 3, see section on supplementary data given at the end of this article), substantial evidence suggests that LIF contributes to reproductive failure (Choudhury & Knapp 2001). In decidua, PIBF is known as a target gene of hsa-miR 520h (Supplementary Table 3), and PIBF can mediate progesterone-induced suppression of decidual lymphocyte cytotoxicity (Laskarin et al 2002). We predicted HLA-DPB1 as a target gene of hsa-miR-520f, which was low expressed in villus (Supplementary Table 3), and just as Takakuwa et al (2003) reported HLA-DPB1 might be a risk allele for unexplained recurrent abortion in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a mediator of progesterone called progesteroneinduced blocking factor blocked the dNK lytic activity [47].…”
Section: Dnk Cells Are Very Unlikely To Play a Role In Cytotoxicitymentioning
confidence: 99%